2009
DOI: 10.1007/s00270-009-9638-z
|View full text |Cite
|
Sign up to set email alerts
|

Sloughing of Intraductal Tumor Thrombus of Hepatocellular Carcinoma After Transcatheter Arterial Chemoembolization

Abstract: Transcatheter arterial chemoembolization (TACE) is effective for hepatocellular carcinoma (HCC) with intrabile duct thrombus. After TACE, intraductal tumor thrombi occasionally detach from the intrahepatic tumor and drop into the bottom of the common bile duct, causing clinical symptoms similar to the impaction of choledocholithiasis. The investigators describe three cases of sloughing of HCC intraductal tumor thrombi after selective TACE. In each of the three cases, the necrotic tumor cast was successfully re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…It is well known that intraductal tumor thrombus is easily detached and excreted into the bile duct after TACE; however, in our experience, necrotic tumor tissues of large HCC without an intraductal tumor thrombus were also excreted into the biliary system after TACE. Thus, the purpose of this study was to retrospectively evaluate the incidence and condition of necrotic tumor excretion into the biliary system in patients with HCC >5 cm.…”
Section: Introductionmentioning
confidence: 51%
“…It is well known that intraductal tumor thrombus is easily detached and excreted into the bile duct after TACE; however, in our experience, necrotic tumor tissues of large HCC without an intraductal tumor thrombus were also excreted into the biliary system after TACE. Thus, the purpose of this study was to retrospectively evaluate the incidence and condition of necrotic tumor excretion into the biliary system in patients with HCC >5 cm.…”
Section: Introductionmentioning
confidence: 51%
“…Our review of the literature identified eight apparent cases (including ours) of obstructive jaundice caused by tumor fragments from HCC after TACE (Table 1). [5][6][7][8][9] The patients (including ours) ranged in age from 62 to 82 years (mean age, 70.5 years) and consisted of five men and three women. Most patients showed bile duct invasion (six of the eight patients) and bile duct dilatation (six of the eight patients) on initial CT finding.…”
Section: 박형철 등 경동맥화학색전술 후 발생한 급성 폐쇄성 담관염mentioning
confidence: 99%
“…However, diagnosis is usually difficult, due to the low incidence rate, ignorance of this disease, and the difficulty of imaging diagnosis to find the BDT. [5][6][7][8][9] The aims of this study were to identify factors that affect tumor migration after TACE. Here, we describe a patient with acute obstructive cholangitis complicated by migration of a necrotic tumor cast after TACE for intrabile duct invasion of HCC and provide a review of the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Migration of intraductal tumour ingrowth to the distal common bile duct, causing obstructive jaundice, rarely occurs following chemoembolization of HCCs with bile duct invasion, which is the so-called 'sloughing' of an intraductal tumour ingrowth [9][10][11][12][13][14][15][16][17][18]. The clinical course of this event remains poorly documented.…”
Section: Introductionmentioning
confidence: 96%